Dawson, Yukon Territory, at the junction of the Klondike and Yukon Rivers. - Curtis, Asahel, 1874-1941 (1929)
Klondike Gold Rush. To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number